Stable anhydrous oral care composition capable of repairing enamel and preparation method thereof
By optimizing the calcium salt, phosphate, arginine and other ingredients in anhydrous toothpaste, and combining appropriate excipients and thickener selection, the problems of stability and usage experience of anhydrous toothpaste paste are solved, achieving better oil retention and convenience of use.
Patent Information
- Application Number
- CN202510198835.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-24
- Publication Date
- 2025-03-21
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
When using calcium salt, phosphate and arginine as active ingredients in existing anhydrous toothpaste, there are problems such as poor oil retention, liquid leakage, thinning of paste shear during paste making, and large changes in consistency during storage, resulting in poor stability and user experience.
By optimizing the type selection, parameter specifications and content of ingredients in anhydrous oral care compositions, especially targeted optimization of functional ingredients such as calcium salts, phosphates, arginine, etc., combined with the selection of appropriate excipients, thickeners and solid fillers, the stability and user experience of the paste are improved. Specific measures include adjusting the dosage of calcium silicate, friction silica and thickened silica, controlling molecular weight and particle size, optimizing the feeding sequence and the speed of the dispersion disk during paste making.
On the basis of not affecting the effective ingredients, the stability and usage experience of the anhydrous oral care composition is greatly improved, the paste stability problem is solved, and the oil retention and convenience of use of the product are improved.
Smart Images

Figure CN119656050A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of daily chemicals, and in particular to a stable anhydrous oral care composition capable of repairing tooth enamel and a preparation method thereof. Background Art
[0002] Toothpaste can be divided into water-containing toothpaste and anhydrous toothpaste (no additional water is added except for the crystal water or moisture contained in the raw materials) according to whether water is added in the formula. Most common toothpastes are water-containing toothpastes, which are mainly composed of excipients, thickeners, functional ingredients, abrasives, foaming agents, fragrances, preservatives, appearance improvers, taste improvers and water. Except for not adding water, the other component types of anhydrous toothpaste are the same as those of water-containing toothpaste.
[0003] At present, many functional ingredients face the same problem when they are used, that is, they are highly reactive and easily react with water, making the functional raw materials ineffective or the toothpaste unstable, and are not suitable for use in aqueous toothpaste formulas. Therefore, in order to ensure the effect of the functional ingredients, such functional ingredients need to be used in anhydrous toothpaste formulas. However, compared with aqueous toothpaste, anhydrous toothpaste also has three problems. First, it is difficult for the product to achieve good efficacy, which affects the product efficacy, user experience and feeling; second, the prepared paste consistency is easy to be too thin or too thick, and difficult to process, which mainly affects the user experience and processing cost; third, the oil retention is poor, it is easy to seep out of liquid and oil, and solid-liquid separation, which not only affects the user experience, but also affects the product efficacy (for example, some functional ingredients can be dissolved or dispersed in the oil phase, while some functional ingredients are solid phases. After solid-liquid separation, the distribution of functional ingredients is uneven, and the relevant efficacy cannot be achieved).
[0004] In the prior art, Chinese patent CN102946847B "Non-aqueous oral care composition" points out that the rheological performance of anhydrous formulas is not like that of typical aqueous toothpastes, and there are problems such as manufacturing difficulties and reduced acceptability among consumers. Therefore, the above problems are solved by adding a special combination of polyethylene glycols, so that the composition has improved microstructure, easy processing and excellent sensory properties, and maintains sufficient stability and functionality at temperatures as low as 5°C and as high as 50°C; however, the solid polyethylene glycol used in the composition is a polyethylene glycol with a large degree of polymerization and a high average molecular weight, and the preparation becomes difficult to extrude, especially at low temperatures. Further, Chinese patent CN103702653B solves this problem by using abrasive amorphous silica. However, the above scheme still cannot improve the oil retention of the formula well, and cannot solve the problem of easy leakage and oil release of the anhydrous formula.
[0005] In the early experiments, it was found that calcium salt, phosphate and arginine as a functional composition can achieve a remineralization effect when applied to the surface of tooth enamel, and can form a repair layer on the surface of tooth enamel, improve the hardness of tooth enamel, increase the Ca / P mass ratio on the surface of tooth enamel, and improve the acid erosion resistance of tooth enamel. However, there are many problems when the composition is used in anhydrous toothpaste, such as poor oil retention of the paste, oil leakage, severe shear thinning of the paste during paste preparation, and large changes in consistency during storage, which makes the paste difficult to squeeze out.
[0006] In summary, the prior art fails to provide an anhydrous oral care composition and a preparation method thereof that contains the above-mentioned effective ingredients (calcium salt, phosphate and arginine) and has good stability and usage experience. Summary of the invention
[0007] In order to solve the above technical problems, firstly, the present invention provides a stable anhydrous oral care composition that can repair tooth enamel. According to the characteristics of the functional ingredients (calcium salt, phosphate, arginine), the present invention has carried out a series of targeted optimizations on the type selection, parameter specifications and content of various components in the anhydrous oral care composition. Ultimately, the stability and use experience of the anhydrous oral care composition can be greatly improved without affecting the efficacy of the functional ingredients, thereby effectively solving a series of paste stability problems when calcium salt, phosphate and arginine are applied to the anhydrous oral care composition. Secondly, the present invention provides a method for preparing a stable anhydrous oral care composition that can repair tooth enamel. The present invention can further improve the stability of the anhydrous oral care composition by optimizing the feeding sequence and controlling the speed of the dispersion disk during the paste making process.
[0008] The specific technical scheme of the present invention is: In a first aspect, the present invention provides a stable anhydrous oral care composition capable of repairing tooth enamel, comprising the following raw materials:
[0009] As described in the background technology section of the present application, it was found in previous experiments that the introduction of calcium salts, phosphates and arginine as effective ingredients into an anhydrous oral care composition, although it can repair tooth enamel to a certain extent, can also cause many problems, such as poor oil retention of the paste, oil exudation, severe shear thinning of the paste during paste preparation, and large changes in consistency during storage, making the paste difficult to squeeze out.
[0010] To this end, the present invention has carried out a series of targeted optimizations on the type selection, parameter specifications and content of various components in the anhydrous oral care composition according to the characteristics of the above-mentioned functional ingredients, and ultimately can greatly improve the stability and use experience of the anhydrous oral care composition without affecting the efficacy of the functional ingredients, thereby effectively solving a series of paste stability problems when calcium salts, phosphates and arginine are used in anhydrous oral care compositions. Specifically: (a) Regarding the functional ingredients: The physical and chemical properties of different functional ingredients vary greatly, and their compatibility with other components also varies greatly. First, regarding calcium salt: calcium salt is preferably calcium silicate; considering that calcium silicate with a suitable oil absorption value can improve the oil retention of the system and is not easy to make the paste thick and hard, the specific surface area of calcium silicate is limited to 700-1000m 2 / kg, oil absorption value = 150-350mL / 100g; at the same time, suitable calcium silicate raw materials can play their efficacy faster and better, so the solubility product constant of calcium silicate is limited to 1×10 -11 -1×10 -7 And the particle size D50=5-10μm, D90=20-30μm. In addition, the amount of calcium silicate is also critical. Too high an amount of calcium silicate can easily lead to a thick paste, and too low an amount of calcium silicate cannot guarantee the effectiveness of repairing enamel. Secondly, regarding phosphates: Considering that inorganic salts often have a significant adverse effect on the thickening effect of organic thickeners, and at the same time, the amount of phosphate affects the effect of repairing enamel, its amount needs to be controlled within an appropriate range. Finally, regarding arginine: Considering that the preparation process of anhydrous toothpaste often requires heating, arginine tends to turn yellow at high temperatures, causing the paste color to change, and the amount of arginine affects the effect of repairing enamel, so its amount also needs to be controlled within an appropriate range.
[0011] (b) Regarding excipients: The present invention finds that if only glycerol is used as an excipient, the paste of the anhydrous oral care composition has a more obvious threading phenomenon, the paste has a poor uprightness, and the use experience is not good; and glycerol has poor compatibility with flavors, which is not conducive to the dissolution of flavors. The material state of polyethylene glycol varies due to its molecular weight difference. Polyethylene glycol with a lower average molecular weight (for example, Mw=200-600) is usually in a liquid state at room temperature, and gradually changes to a semi-solid and solid state as the molecular weight increases. For polyethylene glycol that is liquid at room temperature, it helps to make the system easier to process by reducing the overall viscosity of the continuous liquid phase, especially under high shear. Since polyethylene glycol itself is a surfactant, it can be beneficial to solubilize the flavor, but if its dosage is too high, it is easy to cause the paste to leak oil. For polyethylene glycol that is solid at room temperature, the uprightness of the paste can be improved, and its long chain structure can form a network structure with the organic thickener in the paste to improve the stability of the system. At the same time, it can also provide the best microstructure for the functional ingredients. However, if the amount of solid polyethylene glycol is too high, the consistency of the paste will increase significantly during storage, the paste will be difficult to squeeze out, and the user experience will deteriorate. The higher the molecular weight of polyethylene glycol, the more obvious this phenomenon is. Therefore, the molecular weight and dosage of solid polyethylene glycol should be appropriate. Propylene glycol is a small molecular weight excipient. During the experiment, it was found that when propylene glycol was compounded with glycerol and polyethylene glycol, the paste drawing condition was improved, but the paste was more prone to exudation and oil. Taking all factors into consideration, the excipients were compounded with glycerol, liquid polyethylene glycol, and solid polyethylene glycol.
[0012] (c) About organic thickeners: The commonly used organic thickeners in toothpaste are mainly high molecular compounds, such as xanthan gum, carrageenan, cellulose gum, hydroxypropyl cassia gum, povidone, carbomer, etc. The present invention found that xanthan gum, carrageenan, and cellulose gum do not thicken or have poor thickening effects in anhydrous formula excipients such as glycerol, propylene glycol, and polyethylene glycol under room temperature conditions. Hydroxypropyl cassia gum is a new type of anhydrous formula thickener. When added in an appropriate amount, it can ensure that the paste does not produce oil or seep liquid, and has good stability; but there are problems such as stickiness, obvious stringing, severe yellowing, and uneven paste. Povidone has a good thickening effect in conventional anhydrous formulas, but its compatibility with the active ingredient arginine is poor, and the resulting paste is thin and cannot be used normally; the reason may be that povidone is acidic, and alkaline arginine is not conducive to the formation of hydrogen bonds between povidone and excipients. Carbomer is a polyacrylic acid polymer compound that can form hydrogen bonds with hydroxyl donors such as excipients glycerol, propylene glycol, and polyethylene glycol to achieve a thickening effect. Therefore, the present invention selects carbomer as an organic thickener. The higher the amount of carbomer used, the better the oil retention of the system, but it will cause the paste to harden during storage and be difficult to extrude. In addition, carbomer has poor tolerance to the commonly used foaming agent sodium lauryl sulfate, the effective ingredient phosphate and arginine and is easily affected by shear or homogenization. There is an obvious shear thinning phenomenon in the paste making process, and the obtained paste is relatively thin in the early stage, has poor uprightness, and affects use. Therefore, when using carbomer as an organic thickener, its dosage needs to be controlled; at the same time, other components in the formula also need to be reasonably selected and used to take into account both formula stability and user experience. For example, carbomer is easily affected by the effective ingredients phosphate, arginine, and foaming agent sodium lauryl sulfate, making the prepared paste thinner. Therefore, the effective ingredients phosphate and arginine are preferably in powder form with a smaller particle size to shorten the stirring and dispersion time required for the paste making process and reduce the shear effect. In addition, the dosage of the foaming agents sodium lauryl sulfate, phosphate, and arginine should be appropriately selected.
[0013] (d) Regarding inorganic thickeners: The present invention found that when the conventional inorganic thickener magnesium aluminum silicate is evenly dispersed in glycerin, magnesium aluminum silicate will precipitate after standing for a period of time, and the sample will turn yellow seriously. It can be seen that magnesium aluminum silicate has a poor thickening effect and is easy to affect the appearance of the paste, so it is not suitable for the anhydrous oral care composition. Thickening silica has a large specific surface area and a higher oil absorption value. It is mainly combined with liquid components such as glycerin, liquid polyethylene glycol, and flavors through physical adsorption to improve the oil retention of the system. The present invention found that thickening silica needs to be added in a higher amount to effectively ensure the oil retention of the paste, but accordingly, the paste will dry out and be difficult to extrude during storage. Therefore, it is necessary to strictly control the amount of thickening silica and its oil absorption value.
[0014] (e) Regarding friction agents: The present invention found that friction-type silica has a certain oil absorption value. Although its oil absorption value is significantly lower than that of thickening silica, it still has a certain oil retention within a certain oil absorption value range, so it can improve the stability of the anhydrous formulation system. Through experimental research, the appropriate oil absorption value of friction-type silica is 70-140mL / 100g, and the dosage is 5-20wt%.
[0015] (f) Regarding foaming agents: Sodium lauryl sulfate has a good foaming effect, and it is also a good emulsifier. It can promote the dispersion and dissolution of flavors through emulsification, and make the flavors and other components in the paste evenly combined to form a stable system. Since the organic thickener carbomer is easily affected by sodium lauryl sulfate, the prepared paste is thinner. The amount of sodium lauryl sulfate should balance the foaming performance and the paste state.
[0016] Preferably, the total amount of calcium silicate, frictional silica and thickening silica is 10-26 wt %; the total amount of calcium silicate and thickening silica is 8-16 wt %.
[0017] In the formulation of the present invention, calcium silicate, frictional silica, and thickening silica can all be regarded as solid fillers. Considering that calcium silicate and thickening silica have high oil absorption values, if the stability of the anhydrous formulation system is to be further improved, the total amount of calcium silicate, frictional silica, and thickening silica, as well as the total amount of calcium silicate and thickening silica, should not be too high to avoid the paste from drying up; however, in order to ensure the oil retention of the system, the dosage should not be too low.
[0018] Preferably, the phosphate is orthophosphate with a particle size of D50=10-100 μm and D90=50-200 μm, and is further preferably selected from trisodium phosphate, sodium dihydrogen phosphate and disodium hydrogen phosphate.
[0019] Preferably, the arginine is L-arginine, with a particle size of D50=10-80 μm and D90=50-150 μm.
[0020] Preferably, the liquid polyethylene glycol has an Mw of 200-600, further selected from one or more of polyethylene glycol-200, polyethylene glycol-400 and polyethylene glycol-600; the solid polyethylene glycol has an Mw of 1000-4000, further selected from one or more of polyethylene glycol-1000, polyethylene glycol-1500 and polyethylene glycol-3000.
[0021] Preferably, the appearance improver is selected from one or more of titanium dioxide, mica, pearl powder, pigment and lake.
[0022] Preferably, the taste improver is selected from sucralose and / or saccharin sodium.
[0023] In a second aspect, the present invention provides a method for preparing the above-mentioned anhydrous oral care product composition, which specifically comprises the following steps: 1) Dispersing carbomer in part or all of liquid polyethylene glycol to obtain dispersion A.
[0024] 2) Disperse the remaining liquid polyethylene glycol (if any), solid polyethylene glycol, appearance improver (if any), and taste improver (if any) in glycerol to obtain dispersion B.
[0025] 3) Add dispersion A to dispersion B and mix well to obtain dispersion C.
[0026] 4) Add dispersion C, calcium silicate, phosphate and arginine to the main kettle of the paste making machine and mix them.
[0027] 5) Add thickening silica and friction silica and mix them, evacuate the mixture, stir at 35-50 rpm, and at 600-1000 rpm for the dispersion plate.
[0028] 6) Add foaming agent and flavor (if any) and mix. The speed of the dispersion disk is 600-1000rpm. Continuously vacuum and degas the paste.
[0029] Since shear thinning occurs during the ointment preparation process, in order to further improve the stability of the product, it is preferred that the speed of the dispersion disk be controlled during the ointment preparation process.
[0030] In addition, considering that inorganic salts often have a significant adverse effect on the thickening effect of organic thickeners, and carbomer is easily affected by the effective ingredients phosphate, arginine, and foaming agent sodium dodecyl sulfate, making the prepared paste thinner, the above ingredients should be added as early as possible in the later stage of the paste-making process to reduce the impact.
[0031] Preferably, in 1), the amount of the liquid polyethylene glycol accounts for 40-100% of the total amount of the liquid polyethylene glycol.
[0032] Preferably, in 2), the glycerol is preheated to 55-65°C.
[0033] Preferably, in 3), the dispersion B is cooled to 45-55°C in advance.
[0034] Preferably, in 4), the mixing impeller has a rotation speed of 35-50 rpm and lasts for 5-15 min.
[0035] Preferably, in 5), the vacuum degree of the main kettle of the paste making machine is -0.05~-0.085MPa; the speed of the mixing paddle is 35-50rpm, and the mixing lasts for 5-15min.
[0036] Preferably, in 6), the vacuum degree of the main kettle of the paste making machine is above -0.095 MPa; the rotating speed of the mixing paddle is 35-50 rpm, and the mixing lasts for 5-15 min.
[0037] Compared with the prior art, the beneficial effects of the present invention are: (1) According to the characteristics of the functional ingredients (calcium salt, phosphate, arginine), the present invention has carried out a series of targeted optimizations in the type selection, parameter specifications and content of various ingredients in the anhydrous oral care product composition. Ultimately, the stability and user experience of the anhydrous oral care product composition can be greatly improved without affecting the efficacy of the functional ingredients, thereby effectively solving a series of paste stability problems when calcium salt, phosphate and arginine are used in anhydrous formulas.
[0038] (2) The present invention can further improve the stability of anhydrous toothpaste by optimizing the feeding sequence and controlling the rotation speed of the dispersion disk during the paste making process. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 The stability test results of three commercially available waterless toothpastes, namely, Control Example 1A, Control Example 1B, and Control Example 1C.
[0040] Figure 2 It is a comparison chart of the centrifugal stability test results of the paste samples of different embodiments and reference examples.
[0041] Figure 3 It is a comparison diagram of the paste states of Example 3 and different control examples.
[0042] Figure 4 The following are photos of pastes made with different dispersion disk speeds. DETAILED DESCRIPTION
[0043] The present invention is further described below in conjunction with the embodiments. In a first aspect, a stable anhydrous oral care composition capable of repairing tooth enamel comprises the following raw materials:
[0044] In some preferred implementation cases, the total amount of calcium silicate, frictional silica, and thickening silica is 10-26 wt %; the total amount of calcium silicate and thickening silica is 8-16 wt %.
[0045] In some preferred implementation cases, the phosphate is orthophosphate with a particle size of D50=10-100 μm, D90=50-200 μm, and is further preferably selected from trisodium phosphate, sodium dihydrogen phosphate and disodium hydrogen phosphate.
[0046] In some preferred implementation cases, the arginine is L-arginine, and the particle size D50=10-80 μm, D90=50-150 μm.
[0047] In some preferred implementation cases, the liquid polyethylene glycol has an Mw of 200-600, further selected from one or more of polyethylene glycol-200, polyethylene glycol-400 and polyethylene glycol-600; the solid polyethylene glycol has an Mw of 1000-4000, further selected from one or more of polyethylene glycol-1000, polyethylene glycol-1500 and polyethylene glycol-3000.
[0048] In some preferred implementation cases, the appearance improver is selected from one or more of titanium dioxide, mica, pearl powder, pigment and lake.
[0049] In some preferred embodiments, the taste improver is selected from sucralose and / or saccharin sodium.
[0050] In a second aspect, a method for preparing the anhydrous oral care composition comprises the following steps: 1) Dispersing carbomer in part or all of liquid polyethylene glycol to obtain dispersion A.
[0051] 2) Disperse the remaining liquid polyethylene glycol (if any), solid polyethylene glycol, appearance improver (if any), and taste improver (if any) in glycerol to obtain dispersion B.
[0052] 3) Add dispersion A to dispersion B and mix well to obtain dispersion C.
[0053] 4) Add dispersion C, calcium silicate, phosphate and arginine to the main kettle of the paste making machine and mix them.
[0054] 5) Add thickening silica and friction silica, mix, evacuate, and rotate the dispersion disk at 600-1000 rpm.
[0055] 6) Add foaming agent and flavor (if any) and mix. The speed of the dispersion disk is 600-1000rpm. Continuously vacuum and degas the paste.
[0056] In some preferred implementation cases, in 1), the amount of the partial liquid polyethylene glycol accounts for 40-100% of the total amount of liquid polyethylene glycol.
[0057] In some preferred implementation cases, in 2), the glycerol is preheated to 55-65°C.
[0058] In some preferred implementation cases, in 3), the dispersion B is pre-cooled to 45-55°C.
[0059] In some preferred implementation cases, in 4), the mixing impeller has a rotation speed of 35-50 rpm and lasts for 5-15 min.
[0060] In some preferred implementation cases, in 5), the vacuum degree of the main kettle of the paste making machine is -0.05~-0.085MPa; the rotating speed of the mixing paddle is 35-50rpm, and the mixing lasts for 5-15min.
[0061] In some preferred implementation cases, in 6), the vacuum degree of the main kettle of the paste making machine is above -0.095 MPa; the rotating speed of the mixing agitator is 35-50 rpm, and the mixing lasts for 5-15 minutes.
[0062] Specific examples and comparative examples.
[0063] High-speed centrifugation test is one of the common methods for judging the stability of pastes, which can effectively compare the differences in oil retention of samples. The centrifugal stability evaluation method used is: the paste is placed in a centrifuge tube, centrifuged for 2 hours in a high-speed centrifuge, and the speed is set to 10,000 rpm, and the paste exudation, oil release, stratification, solid-liquid separation, etc. are observed and compared.
[0064] 1. Centrifugal stability of several commercially available toothpastes
[0065] Comparative Example 1A, Comparative Example 1B, and Comparative Example 1C are three common commercially available waterless toothpastes. They were subjected to centrifugal stability tests. The test results are as follows: Figure 1 As shown, all three toothpastes showed obvious liquid seepage, oil leakage, and solid-liquid separation.
[0066] (II) The total amount of calcium silicate, friction silica, and thickening silica used in the paste making process, and the comparison of the effects of the total amount of calcium silicate and thickening silica on the paste state or stability
[0067] Note: The unit of specific surface area is m 2 / kg, the unit of oil absorption value is mL / 100g, and the unit of particle size is μm.
[0068] The preparation method of the above toothpaste sample is as follows: Step 1: Take 80% liquid polyethylene glycol, add carbomer into it and disperse evenly; Step 2: After heating the glycerol to 60° C., add the remaining liquid polyethylene glycol and solid polyethylene glycol into the glycerol and disperse them evenly; Step 3: Add the dispersion prepared in step 1 to the dispersion prepared in step 2, wherein the temperature of the dispersion in step 2 needs to be reduced to 48°C, and stir for 45 minutes; Step 4: Add the dispersion obtained in step 3 to the main kettle of the paste making machine, then add calcium silicate, phosphate, and arginine, turn on the stirring paddle, set the stirring paddle speed to 40 rpm, and continue for 15 minutes; Step 5: Continue to add thickening silica and friction silica to the main kettle, turn on the stirring paddle and dispersion disk, set the stirring paddle speed to 40 rpm, and the dispersion disk speed to 800 rpm, continue for 15 minutes, and set the vacuum degree to -0.085 MPa; Step 6: Continue to add foaming agent and flavor to the main kettle, turn on the stirring paddle and dispersion disk, set the stirring paddle speed to 40rpm, and the dispersion disk speed to 800rpm, and continue for 10 minutes. During this step, vacuum is continuously drawn and the paste is degassed throughout the process, and the vacuum degree is maintained above -0.095MPa.
[0069] The paste state or stability of the anhydrous toothpastes of the above embodiments and control examples was tested, and the results were as follows:
[0070] The total amount of calcium silicate, frictional silica, and thickening silica in the formula, and the total amount of calcium silicate and thickening silica were compared between Example 1, Example 2, Control Example 2A, Control Example 2B, and Control Example 2C. The amounts used in Example 1 and Example 2 are appropriate, and the prepared paste has good centrifugal stability, and no obvious oil seepage, solid-liquid separation, or stratification occurs. The total amount of calcium silicate, frictional silica, and thickening silica used in Control Example 2A, as well as the total amount of calcium silicate and thickening silica used, are all low, resulting in poor oil retention in the formula, poor centrifugal stability of the prepared paste, and obvious oil seepage, solid-liquid separation, such as Figure 2 As shown in . The total amount of calcium silicate and thickening silica in control example 2B is relatively high, and the total amount of calcium silicate, friction silica, and thickening silica in control example 2C is relatively high. The prepared paste is relatively thick, dries up during storage, is difficult to squeeze out, and has a poor user experience. Figure 3 as shown in .
[0071] (III) Comparison of the effects of oil absorption values of frictional silica and thickening silica on the paste state or stability of anhydrous toothpaste during the paste making process
[0072] Note: The unit of specific surface area is m 2 / kg, the unit of oil absorption value is mL / 100g, and the unit of particle size is μm.
[0073] The preparation method of the above toothpaste sample is as follows: Step 1: Take 90% liquid polyethylene glycol, add carbomer into it and disperse evenly; Step 2: After heating the glycerol to 60° C., add the remaining liquid polyethylene glycol and solid polyethylene glycol into the glycerol and disperse them evenly; Step 3: Add the dispersion prepared in step 1 to the dispersion prepared in step 2, wherein the temperature of the dispersion in step 2 needs to be reduced to 50°C, and stir for 60 minutes; Step 4: Add the dispersion obtained in step 3 to the main kettle of the paste making machine, then add calcium silicate, phosphate, and arginine, turn on the stirring paddle, set the stirring paddle speed to 35 rpm, and continue for 15 minutes; Step 5: Continue to add thickening silica and friction silica to the main kettle, turn on the stirring paddle and dispersion disk, set the stirring paddle speed to 35 rpm, and the dispersion disk speed to 800 rpm, continue for 15 minutes, and set the vacuum degree to -0.07 MPa; Step 6: Continue to add foaming agent and flavor to the main kettle, turn on the stirring paddle and dispersion disk, set the stirring paddle speed to 35rpm, and the dispersion disk speed to 800rpm, and continue for 15 minutes. During this step, vacuum is continuously drawn and the paste is degassed throughout the process, and the vacuum degree is maintained above -0.095MPa.
[0074] The paste state or stability of the anhydrous toothpaste of the above-mentioned Example 3 and each control example was tested, and the results were as follows:
[0075] The effects of friction silica oil absorption value and thickening silica oil absorption value on the paste state and stability were compared between Example 3, Comparative Example 3A, and Comparative Example 3B. The friction silica used in Comparative Example 3A had a lower oil absorption value and poor oil retention. The resulting paste had poor centrifugal stability and obvious oil seepage and solid-liquid separation. Figure 2 The thickening silica used in Comparative Example 3B has too high an oil absorption value, and the resulting paste is relatively thick, dries up during storage, is difficult to squeeze out, and has a poor user experience. Figure 3 as shown in .
[0076] 4. Comparison of the effects of excipient types and models on the paste state or stability of anhydrous toothpaste
[0077] Note: The unit of specific surface area is m 2 / kg, the unit of oil absorption value is mL / 100g, and the unit of particle size is μm.
[0078] The preparation method of the above toothpaste sample is as follows: Step 1: Take 100% liquid polyethylene glycol, add carbomer into it and disperse evenly; Step 2: After heating glycerol to 60° C., solid polyethylene glycol is added into the glycerol and dispersed evenly; Step 3: Add the dispersion prepared in step 1 to the dispersion prepared in step 2, wherein the temperature of the dispersion in step 2 needs to be reduced to 52°C, and stir for 50 minutes; Step 4: Add the dispersion obtained in step 3 to the main kettle of the paste making machine, then add calcium silicate, phosphate, and arginine, turn on the stirring paddle, set the stirring paddle speed to 40 rpm, and continue for 15 minutes; Step 5: Continue to add thickening silica and friction silica to the main kettle, turn on the stirring paddle and dispersion disk, set the stirring paddle speed to 40 rpm, and the dispersion disk speed to 900 rpm, continue for 15 minutes, and set the vacuum degree to -0.085 MPa; Step 6: Continue to add foaming agent and flavor to the main kettle, turn on the stirring paddle and dispersion disk, set the stirring paddle speed to 40rpm, and the dispersion disk speed to 900rpm, and continue for 10 minutes. During this step, vacuum is continuously drawn and the paste is degassed throughout the process, and the vacuum degree is maintained above -0.095MPa.
[0079] The paste state or stability of the anhydrous toothpastes of the above embodiments and control examples was tested, and the results were as follows:
[0080] The effects of the types and models of excipients on the paste state and stability were compared between Example 4, Example 5, Control Example 4A, and Control Example 4B. The molecular weight of the liquid polyethylene glycol used in Control Example 4A was too high, and the solubilization effect in the system was poor. The paste obtained had poor centrifugal stability, and slight tube mouth seepage and solid-liquid separation occurred. Control Example 4B added the excipient propylene glycol, and the paste obtained had poor centrifugal stability, and oil seepage and solid-liquid separation occurred at the tube mouth and tube tail. Figure 2 as shown in .
[0081] 5. Comparison of the effect of arginine particle size on the paste state or stability of anhydrous toothpaste during the paste preparation process
[0082] Note: The unit of specific surface area is m 2 / kg, the unit of oil absorption value is mL / 100g, and the unit of particle size is μm.
[0083] The preparation method of the above toothpaste sample is as follows: Step 1: Take 100% liquid polyethylene glycol, add carbomer into it and disperse evenly; Step 2: After heating glycerol to 60° C., solid polyethylene glycol is added into the glycerol and dispersed evenly; Step 3: Add the dispersion prepared in step 1 to the dispersion prepared in step 2, wherein the temperature of the dispersion in step 2 needs to be reduced to 55°C, and stir for 30 minutes; Step 4: Add the dispersion obtained in step 3 to the main kettle of the paste making machine, then add calcium silicate, phosphate, and arginine, turn on the stirring paddle, set the stirring paddle speed to 35 rpm, and continue for 10 minutes; Step 5: Continue to add thickening silica and friction silica to the main kettle, turn on the stirring paddle and dispersion disk, set the stirring paddle speed to 35 rpm, and the dispersion disk speed to 1000 rpm, continue for 15 minutes, and set the vacuum degree to -0.08 MPa; Step 6: Continue to add foaming agent and flavor to the main kettle, turn on the stirring paddle and dispersion disk, set the stirring paddle speed to 35rpm, and the dispersion disk speed to 1000rpm, and continue for 5 minutes. During this step, vacuum is continuously drawn and the paste is degassed throughout the process, and the vacuum degree is maintained above -0.095MPa.
[0084] The paste state or stability of Example 6 and Comparative Example 5A was tested, and the results were as follows:
[0085] The effect of arginine particle size on the paste state and stability was compared between Example 6 and Control Example 5A. The arginine particle size used in Control Example 5A was too large, and it was dispersed in the paste during the paste making process, and gradually precipitated in the paste as the paste consistency increased. During the stability test, the appearance of the paste became rough and not smooth, as shown in FIG. Figure 3 as shown in .
[0086] (VI) Comparison of the effect of the dispersion disk speed on the paste state or stability of anhydrous toothpaste during the paste making process
[0087] Note: The unit of specific surface area is m 2 / kg, the unit of oil absorption value is mL / 100g, the unit of particle size is μm, and the unit of dispersion disk speed is rpm.
[0088] The preparation method of the above toothpaste sample is as follows: Step 1: Take 80% liquid polyethylene glycol, add carbomer into it and disperse evenly; Step 2: After heating the glycerol to 60° C., add the remaining liquid polyethylene glycol and solid polyethylene glycol into the glycerol and disperse them evenly; Step 3: Add the dispersion prepared in step 1 to the dispersion prepared in step 2, wherein the temperature of the dispersion in step 2 needs to be reduced to 50°C, and stir for 60 minutes; Step 4: Add the dispersion obtained in step 3 to the main kettle of the paste making machine, then add calcium silicate, phosphate, and arginine, turn on the stirring paddle, set the stirring paddle speed to 35 rpm, and continue for 15 minutes; Step 5: Continue to add thickening silica and friction silica to the main kettle, turn on the stirring paddle and dispersion disk, set the stirring paddle speed to 35 rpm, and the dispersion disk speed to 300-1500 rpm, continue for 15 minutes, and set the vacuum degree to -0.085 MPa; Step 6: Continue to add foaming agent and flavor to the main kettle, turn on the stirring paddle and dispersion disk, set the stirring paddle speed to 35rpm, and the dispersion disk speed to 300-1500rpm, and continue for 10 minutes. During this step, vacuum is continuously drawn and the paste is degassed throughout the process, and the vacuum degree is maintained above -0.095MPa.
[0089] The paste state or stability of the anhydrous toothpaste of Example 7 and Comparative Examples 6A and 6B was tested, and the results were as follows:
[0090] The effect of the dispersion disk speed during the paste making process was compared between Example 7, Control Example 6A, and Control Example 6B. The dispersion disk speed of Example 7 was appropriate, and the prepared paste did not have lumps or uneven dispersion, and the paste did not show obvious shear thinning. In Control Example 6A, the dispersion disk speed during the paste making process was low, and the prepared paste showed obvious unevenness. In Control Example 6B, the dispersion disk speed during the paste making process was high, and the paste showed obvious shear thinning. Figure 4 shown.
[0091] The raw materials and equipment used in the present invention, unless otherwise specified, are all commonly used raw materials and equipment in the art; the methods used in the present invention, unless otherwise specified, are all conventional methods in the art.
[0092] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent transformation made to the above embodiment based on the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. A stable anhydrous oral care composition for repairing tooth enamel, characterized in that Including the following ingredients: Effective ingredients: Calcium silicate 2-20wt%, specific surface area 700-1000m 2 / kg, oil absorption value 150-350mL / 100g, solubility product constant 1×10 -11 -1×10 -7 , particle size D50=5-10μm, D90=20-30μm; phosphate 0.5-10wt%; arginine 0.5-5wt%; Excipients: glycerol 8-80wt%; liquid polyethylene glycol 5-15wt%; solid polyethylene glycol 0.5-5wt%; Organic thickener: Carbomer 0.2-1wt%; Inorganic thickener: thickening silica 0.5-10wt%, oil absorption value 250-330mL / 100g; Friction agent: friction type silica 5-20wt%, oil absorption value 70-140mL / 100g; Other components: foaming agent sodium lauryl sulfate 1-2wt%; flavor 0-1.5wt%; appearance improver 0-0.3wt%; taste improver 0-0.3wt%.
2. The anhydrous oral care composition according to claim 1, characterized in that: The total amount of calcium silicate, friction-type silica and thickening-type silica is 10-26wt%; The total amount of the calcium silicate and thickening silicon dioxide is 8-16 wt %.
3. The anhydrous oral care composition according to claim 1, characterized in that: The phosphate is orthophosphate, with a particle size of D50=10-100 μm and D90=50-200 μm; The arginine is L-arginine, and the particle size D50 is 10-80 μm, and D90 is 50-150 μm.
4. The anhydrous oral care composition according to claim 1, characterized in that: The liquid polyethylene glycol has a Mw of 200-600; The solid polyethylene glycol has a Mw of 1000-4000.
5. A method for preparing the anhydrous oral care composition according to any one of claims 1 to 4, characterized in that include: 1) mixing liquid polyethylene glycol dispersed with carbomer and glycerol dispersed with solid polyethylene glycol, optional liquid polyethylene glycol, optional appearance improver, and optional taste improver to obtain a dispersion; 2) Mix the dispersion with calcium silicate, phosphate and arginine in the main kettle of the ointment making machine; 3) Add thickening silica and friction silica, mix, evacuate, and rotate the dispersion disk at 600-1000 rpm; 4) Add foaming agent and optional flavor and mix, with the dispersion disk rotating at 600-1000rpm, and continuously vacuum and degas.
6. The preparation method according to claim 5, characterized in that: 1) In The preparation method of the glycerol dispersed with solid polyethylene glycol, optional liquid polyethylene glycol, optional appearance improver, and optional taste improver is: preheating the glycerol to 55-65°C, dispersing the solid polyethylene glycol, optional liquid polyethylene glycol, optional appearance improver, and optional taste improver in the glycerol, and then cooling it to 45-55°C.
7. The preparation method according to claim 5 or 6, characterized in that: 1), the amount of the liquid polyethylene glycol dispersed with carbomer accounts for 40-100% of the total amount of the liquid polyethylene glycol.
8. The preparation method according to claim 5, characterized in that: 2), the mixing impeller has a rotation speed of 35-50 rpm and lasts for 5-15 min.
9. The preparation method according to claim 5, characterized in that: 3) In The vacuum degree of the main kettle of the paste making machine is -0.05~-0.085MPa; The mixing paddle has a rotation speed of 35-50 rpm, and the mixing lasts for 5-15 min.
10. The preparation method according to claim 5, characterized in that: 4) In The vacuum degree of the main kettle of the paste making machine is above -0.095MPa; The mixing paddle has a rotation speed of 35-50 rpm, and the mixing lasts for 5-15 min.
Citation Information
Patent Citations
Non-aqueous oral care composition
CN102946847B
non-aqueous oral care composition
CN103702653B
Non-aqueous oral care compositions
CN102946847A
Preparation method of friction type silicon dioxide
CN106276929A
Anhydrous oral care composition capable of repairing enamel and application thereof
CN117180118A